Association between asthma and cardiovascular disease: evidence from the national health and nutrition examination survey 1999–2018 - Peng, Biao; Zhao, Wenjing; Wan, Fang; Ji, Zhonghai; Luo, Runkun; Wang, Sheng; Cao, Anhua; Yang, Zhichao; Liu, Da; Tang, Changchun; Deng, Ping (Frontiers in Cardiovascular Medicine, 2024)
BackgroundCardiovascular disease(CVD) remains a significant global challenge. Asthma, which is characterized by airway hyperresponsiveness and reversible and limited airflow, plays an important role in cardiovascular diseases. This study aimed to investigate the association between asthma and CVD.MethodsThis cross-sectional study included demographic, laboratory, and questionnaire data from the National Health and Nutrition Examination Survey (NHANES) 1999–2018. CVD included stroke, congestive heart failure, coronary heart disease, and angina. Multiple logistic regression models were used to detect the association between asthma and the prevalence of CVD, adjusting for age, gender, race, education level, body mass index, ratio of family income to poverty, smoking exposure, drinking exposure, diabetes history, hypertension history, chronic obstructive pulmonary disease (COPD) history, and chronic kidney disease (CKD) history. A subgroup analysis was performed to investigate the association between asthma and CVD in different populations.ResultsIn total, 16,807 participants were included in this study, including 2,446 who reported having asthma. Compared with participants without asthma, the prevalence of stroke in those with asthma was increased by 1.607 times; the prevalence of congestive heart failure was increased by 1.911 times. Asthma significantly increased the prevalence of stroke among participants aged 18–44 years old, with a BMI 18.50–29.99 kg/m2, with low education levels, and with a PIR < 1.00. Asthma also increased the prevalence of angina in females, non-Hispanic Blacks, participants aged 45–59 years old, with a BMI ≥ 30.00 kg/m2, and with a PIR < 1.00. The prevalence of congestive heart failure was positively associated with asthma in non-Hispanic Whites or Blacks, participants aged ≥45 years old, with a BMI 25.00–29.99 kg/m2, with a PIR < 1.00, and with a low or middle education level.ConclusionAsthma significantly increases the prevalence of stroke, congestive heart failure. Patients with asthma should be monitored for CVD, including stroke and congestive heart failure.